A revision of Tripanda and Tenerva (Hemiptera: Heteroptera: Pentatomidae: Pentatominae) - Kment, Petr; Jindra, Zdeněk (Zootaxa, 2009)
The Afrotropical genus Tripanda Berg, 1899 (Heteroptera: Pentatomidae: Pentatominae: Cappaeini), is diagnosed and revised based on the study of primary types. The endemic Madagascar genus Tenerva Cachan, 1952, syn. et stat nov., is recognized as a junior synonym of Tripanda, but retained as a valid subgenus due to the distinct differences in the structure of the female genitalia. Veterna decorata Jensen-Haarup, 1937, is redescribed and transferred to Tripanda (subgenus Tenerva). We currently recognize seven species within the genus: Tripanda (Tenerva) collaris (Cachan, 1952) comb. nov. (Madagascar); T. (Tenerva) decorata (Jensen-Haarup, 1937) comb. nov. (Namibia, South Africa, Zambia, Zimbabwe; Yemen); T. (Tripanda) dispar Schouteden, 1964 (Democratic Republic of the Congo, Ivory Coast, Nigeria, Republic of the Congo); T. (Tripanda) horacekorum sp. nov. (Central African Republic, Gabon, Ghana, Ivory Coast, Nigeria, Republic of the Congo, Senegal); T. (Tripanda) jurickorum sp. nov. (Guinea); T. (Tripanda) longiceps (Villiers, 1967) (Central African Republic, Ghana, Guinea, Ivory Coast, Republic of the Congo); and T. (Tripanda) signitenens (Distant, 1898) (Angola, South Africa, Tanzania, Zambia). Lectotypes for Tenerva collaris, Veterna decorata, Tripanda dispar, and T. signitenens are designated. All species of the genus are keyed, important diagnostic characters are illustrated, and known information about their bionomics and ecology is summarized.